Widening perspectives on social impact bonds. Issue 1 (2nd January 2021) - Tan, Stefanie; Fraser, Alec; McHugh, Neil; Warner, Mildred E.
ABSTRACT: Social Impact Bonds (SIBs) are a novel financing mechanism for public services delivery. This special issue about SIBs in the UK argues that they necessitate closer examination to understand the implications for all stakeholders. This introductory paper critically explores and challenges dominant practitioner narratives of SIBs as "win-win" solutions for governments and service providers. While SIBs may foster innovation it is unclear if they deliver better value given the complexity of public services. SIBs are a strategically ambiguous policy tool and policymakers should be cautious about SIBs due to contractual complexity and issues with ethics, governance, accountability and transparency.